Quantitative analysis of movements in facial nerve palsy with surface electromyography and kinematic analysis. (February 2021) - Demeco, A.; Marotta, N.; Moggio, L.; Pino, I.; Marinaro, C.; Barletta, M.; Petraroli, A.; Palumbo, A.; Ammendolia, Antonio
Abstract: Facial nerve paralysis (FNP) has a significant effect on a person's quality of life. In individuals with FNP undergoing facial rehabilitation, methods to analyze the loss of function are useful in diagnosis, treatment and follow up. To propose a protocol with kinematic analysis coupled with sEMG to evaluate the outcomes of FNP, quantifying the excursion degrees of the facial muscles and symmetry of voluntary movements. 10 patients (Group A) were followed by diagnosis until the end of the rehabilitation program. Kinematic analysis of 20 healthy adults (group B) was performed as a starting point to have a normality range and to test intra-subject and inter- intra rater reliability. An optoelectronic system and sEMG wireless electrodes were used. In Group A, a significant improvement in the movement of frontalis muscle (P = 0.0118) after 4-week treatment from the beginning (T0) 9.8 ± 4.5 mm to the end of rehabilitation (T1) 16.3 ± 5.8 mm and orbicularis oris (P = 0.0143) from T0 14.8 ± 5.5 mm to T1 20.3 ± 3.3 mm and, a reduction of % of maximum voluntary contractions (MVC) at T1 for frontalis and orbicularis compared to T0. This protocol provides meaningful data in a simple, reliable and objective way for the functional assessment of patients with PNF.